The experience of women with recent gestational diabetes during the COVID-19 lockdown: a qualitative study from Denmark - Nanna Husted Jensen; Karoline Kragelund Nielsen; Inger Katrine Dahl-Petersen; Helle Terkildsen Maindal (BMC, 2022)
Abstract Background Following COVID-19 and the lockdowns, maternity care and support for women after delivery have been temporary restructured. Studies show that COVID-19 adversely impacts pregnant and peripartum women in the general population, but experiences among women in the first year after delivery/in the wider postpartum period remain unexplored. Moreover, experiences among women with recent gestational diabetes mellitus (GDM) are lacking; though it is a group with a potential high need for support after delivery. The aim of our study was to investigate (i) how women with recent GDM experienced COVID-19 and the first lockdown in Denmark, and (ii) the women's risk perception and health literacy in terms of interaction with the healthcare system in relation to COVID-19. Methods We performed a qualitative study among 11 women with recent GDM (infants aged 2-11 months old). Semi-structured interviews were conducted in April-May 2020 by telephone or Skype for Business, when Denmark was under lockdown. We analysed data using a thematic qualitative content analysis. Results Three themes emerged: i) Everyday life and family well-being, ii) Worries about COVID-19 and iii) Health literacy: Health information and access to healthcare. The women were generally not worried about their own or their infant's risk of COVID-19. The lockdown had a negative impact on everyday life e.g. routines, loneliness, breastfeeding uncertainties and worries for the infant's social well-being; but better family dynamics were also described. It was challenging to maintain healthy behaviours and thus the women described worries for the risk of type 2 diabetes and GDM in subsequent pregnancies. The women missed peer support and face-to-face visits from health visitors and found it difficult to navigate the restructured care with online/telephone set-ups. Conclusions COVID-19 and the lockdown affected everyday life among women with recent GDM both positively and negatively. Our findings suggest a need for care that are responsive to psychological and social aspects of health throughout the COVID-19 pandemic and support to limit worries about adaptation to motherhood and the infant's social well-being. Communication focusing on the importance and relevance of contacting healthcare providers should also be strengthened.